Polarization of the hard bremsstrahlung of the relativistic electrons in a crystal - Kasian, S.V.; Morokhovskii, V.L. (Вопросы атомной науки и техники, 2007)
Results of the polarization measurements of high energy bremsstrahlung in crystals are presented. For analysis of the photon polarization the asymmetry of the yields of the single p-meson photo-production on proton was used. The asymmetry of the yields of products of p-meson photo-production on the liquid-hydrogen target are presented for bremsstrahlung photons with energy Eγ = 700 MeV generated by electrons with energy Eₑ₋ = 800 MeV in the Si-crystal targets with thickness 120 µm and 30 µm. The properties of the high energy bremsstrahlung in crystals for the cases of electron beam orientations under the small angles respectively to the crystal axis (111) and plane (110) are investigated.